2017
DOI: 10.1123/ijsnem.2017-0038
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Changes Following Competition in Male and Female Physique Athletes: A Pilot Study

Abstract: The purpose of the current study was to evaluate changes in body composition, metabolic rate, and hormones during postcompetition recovery. Data were collected from natural physique athletes (7 male/8 female) within one week before (T1) competition, within one week after (T2), and 4-6 weeks after (T3) competition. Measures included body composition (fat mass [FM] and lean mass [LM] from ultrasongraphy), resting metabolic rate (RMR; indirect calorimetry), and salivary leptin, testosterone, cortisol, ghrelin, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(57 citation statements)
references
References 0 publications
7
50
0
Order By: Relevance
“…6 In the current study, the FA reached their lowest mean BF% of 17% at T2, while case studies of FA have reported levels of 9%-11% [14][15][16][17] and cohort studies means of 13%-18%. [20][21][22] Importantly, in the previous case studies, menstrual disturbances were reported to occur early during the dieting, 14,17 suggesting such impairments may be a response to the LEA rather than a specific level of BF%.…”
Section: F I G U R E 4 Changes In Body Weightmentioning
confidence: 88%
See 4 more Smart Citations
“…6 In the current study, the FA reached their lowest mean BF% of 17% at T2, while case studies of FA have reported levels of 9%-11% [14][15][16][17] and cohort studies means of 13%-18%. [20][21][22] Importantly, in the previous case studies, menstrual disturbances were reported to occur early during the dieting, 14,17 suggesting such impairments may be a response to the LEA rather than a specific level of BF%.…”
Section: F I G U R E 4 Changes In Body Weightmentioning
confidence: 88%
“…3,4 Hence, there are reasons for concern for the health of these athletes. At the time, only four case studies [14][15][16][17] and four cohort publications [18][19][20][21] report on health outcomes in females related to dieting for fitness sport participation. Among the publications with post-competition measures, 14,17,20,21 changes in BW and composition were reported to be temporary, with return to or above baseline 14,17,20 or normal, healthy levels 21 within 1-4 months post-dieting.…”
mentioning
confidence: 99%
See 3 more Smart Citations